La Tutela Jurisdiccional y la Legitimidad para obrar en los Procesos Laborales sobre Desnaturalizaciòn de la Subcontrataciòn Empresarial - Otiniano Espinoza, Dina Corina (2019)
The present investigation has as purpose exposing the problematic that originates around the emplacement of subcontractors companies in the processes where the controvertial object is about denaturation of intermediation and / or labor outsourcing, and is that, when forming part of the juridical procedural relation these productive outsourcing companies violate the effective jurisdictional protection, because the material rule that resolves the case does not establish any legal consequence for the aforementioned companies, generating unnecessary delays in the resolution of the processes among other economic and administrative cost overruns. This hypothesis is based on a doctrinal, legal and casuistic analysis, concluding that it is inofficious to inform the intermediary and outsourcing companies of these processes.